A Systematic Literature Review on Interfacial Tension and Zeta Potential Analyses Behind Smart Waterflooding - Riswati, Shabrina Sri; Prakoso, Suryo; Setiati, Rini; Fathaddin, Muhammad Taufiq (Universitas Islam Riau (UIR) Press, 2024)
Smart waterflooding is a widely discussed topic for oil recovery improvement, with the main mechanism believed to be wettability alteration. However, the exact phenomena behind this effect are still being debated. This systematic literature review (SLR) utilized the Scopus database to analyze and assess studies on the interfacial tension (IFT) and zeta potential (ZP) concepts and their impact on smart waterflooding between 2017 and 2021. The review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. The review found inconsistencies in the literature, with some studies suggesting that the reduction of IFT from smart waterflooding was not the reason for oil recovery improvement. Further evidence on the alteration of surface charge through ZP analysis is needed, and gaps are present in the area of simulation approach. The study suggests that improvements in model development and experimental setup design are necessary for future studies to obtain comprehensive conclusions. In summary, this SLR provides a critical overview of the recent understanding of the impact of IFT and ZP on smart waterflooding and highlights areas for further research, including a potential model that incorporates each mechanism with the ultimate oil recovery.